A study of the promotion mechanism of digital inclusive finance for the common prosperity of Chinese rural households - Zhang, Mei; Zhu, Tianyu; Huo, Zenghui; Wan, Peng (Frontiers in Earth Science, 2024)
Common prosperity is a social policy goal pursued by the Chinese government and an ideal social status for humanity. On the basis of three theoretical hypotheses, this study involved the analysis of county-level digital inclusive finance data and rural survey data. The Hierarchical Linear Model was employed to empirically analyze the impact and mechanism of digital inclusive finance on the common prosperity of rural households. The results indicate that the county-level digital inclusive finance index, as well as its depth and coverage, can significantly and directly promote common prosperity. Furthermore, it was found that household livelihood strategies are one of the regulatory mechanisms, and digital inclusive finance significantly promotes common prosperity through factors such as opportunities for migrant work, property income, business livelihood models, and agricultural livelihood models. In addition, financing methods are also important adjustment mechanisms, and digital inclusive finance significantly promotes the common prosperity through digital tools and loan availability variables. Our research provides favorable evidence for the crosslevel interaction effect of county-level digital inclusive finance on the common prosperity of rural households.